A new Tetranchyroderma species (Gastrotricha, Macrodasyida) from Tunisia, with its phylogenetic position based on molecular markers - Souid, Aicha; Gammoudi, Mehrez; Cafsi, M’hamed El; Cesaretti, Agata; Kosakyan, Anush; Saponi, Francesco; Todaro, M. Antonio (Zootaxa, 2026)
Data on marine gastrotrichs fauna from the southern coast of the Mediterranean Sea is scanty. To address the gap, a series of faunistic surveys along the northern Tunisian coastline is ongoing. In a shallow sublittoral sample collected at Chat Zwerâa, Béja, a new species of the genus Tetranchyroderma was found. Detailed morphological descriptions, along with molecular phylogenetic analysis based on ribosomal genes (18S and 28S) of the new species are provided. The new Tetranchyroderma has a pentancrous covering and prominent cephalic pestle organs; the caudal pedicles have three tubes each. The new species is also defined by a number and arrangement of adhesive tubes different from its congeners. Phylogenetic analyses using maximum likelihood (ML) and Bayesian inference (BI) methods, based on concatenated ribosomal gene sequences from 43 taxa, which included 31 thaumastodermatids, confirmed that the genus Tetranchyroderma is non-monophyletic. The analysis positioned the new species alongside other species that possess pestle organs, including Tetranchyroderma antenniphorum, T. esarabdophorum, T. papii and Ptychostomella tyrrhenica.